Endoscopia do trato gastrointestinal de cães e gatos - Legatti, Emerson [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Endoscopy of the gastrointestinal tract is a specialized minimally invasive diagnostic method and with both diagnostic and therapeutic possibilities. It is divided into two major groups, the rigid and flexible endoscopy. The first most widely used for visualization of body cavities that do not have a light, like the chest, for example, and the second for those with light as the gastrointestinal tract. In Brazil there are few professionals, veterinary hospitals or clinics that offer this type of service. Thus, endoscopy is an area of expertise of the veterinarian who is in huge expansion and has shown great applicability with excellent results in both clinical medicine and surgical small animals

A endoscopia do trato gastrointestinal é um método diagnóstico especializado minimamente invasivo e com possibilidades tanto diagnósticas quanto terapêuticas. É dividida em dois grandes grupos, a endoscopia rígida e a flexível. A primeira mais utilizada para visibilização de cavidades corpóreas que não possuem uma luz, como o tórax por exemplo, e a segunda para as que possuem luz, como o trato gastrointestinal. No Brasil ainda são poucos os profissionais, clínicas ou hospitais veterinários que oferecem este tipo de serviço. Sendo assim, a endoscopia é uma área de atuação do médico veterinário que se encontra em ampla expansão e vem demonstrando grande aplicabilidade com ótimos resultados na clínica médica e cirúrgica de pequenos animais
Keywords: Cão; Gato; Sistema gastrointestinal - Doenças; Endoscopios